2019
DOI: 10.1002/ijch.201900062
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquids‐Based Membranes for Carbon Dioxide Separation

Abstract: Ionic liquids (ILs) have gained wide‐spread focus owing to its negligible vapor pressure, low heat capacity, high thermal stability, and structural diversity. The solubility and selectivity toward carbon dioxide has made ILs a unique platform that possess the potential in gas separations. In particularly, combining functional ILs with membranes and porous supports is an efficient way to design task‐specific materials for CO2 separations. This minireview summarizes the developments and advances of ionic liquids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…[9,10] Recently, the supported ionic liquid membrane (SILM) has been reported for CO 2 separation. [11][12][13] SILM is a composite membrane, in which ionic liquids are occluded into a porous support. [14] The intrinsic properties of ionic liquid, such as non-volatility, high viscosity, high thermal and chemical stability, [15,16] make the SILM advantageous in CO 2 separation over the traditional supported liquid membranes, which usually suffer from severe liquid loss caused by either volatilization or displacement during the use.…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] Recently, the supported ionic liquid membrane (SILM) has been reported for CO 2 separation. [11][12][13] SILM is a composite membrane, in which ionic liquids are occluded into a porous support. [14] The intrinsic properties of ionic liquid, such as non-volatility, high viscosity, high thermal and chemical stability, [15,16] make the SILM advantageous in CO 2 separation over the traditional supported liquid membranes, which usually suffer from severe liquid loss caused by either volatilization or displacement during the use.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the disadvantages of supported liquid membranes, scientists started to use ionic liquids instead of conventional solvents. Supported ionic liquid membranes (SILMs) have been the object of interest of many research groups for the last twenty years, as highlighted by the number of published reviews [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. The new types of SILMs created have high selectivity and permeability, and they combine the advantage of the stripping process by liquids with high solubility and the easy operation of membranes.…”
Section: Supported Ionic Liquid Membranesmentioning
confidence: 99%
“…PILs preserve many of the beneficial properties of ILs such as thermal and chemical stability and ion conductivity. Moreover, PILs benefit from the intrinsic polymer properties [ 23 , 107 , 108 ]. In comparison with usual polyelectrolytes, the PILs are not soluble in water, but generally in polar organic solvents only [ 107 ].…”
Section: Polymeric Ionic Liquids (Pils)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent pilot-scale trials at power plants in Germany showed that optimized SILMs could maintain their structural and process stability for 335 h [11]. The success of SILMs is well highlighted in recently published reviews [4,[12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%